2013
DOI: 10.1007/s13277-013-1308-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of serum hepatocyte growth factor (HGF) levels in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the commonest primary malignant cancer of the liver in the world. This study was conducted to investigate the serum levels of hepatocyte growth factor (HGF)in HCC patients and the relationship with tumor progression and known prognostic parameters. Fifty-four patients with HCC were investigated. Pretreatment HGF levels were employed the quantitative sandwich enzyme immunoassay technique (ELISA). Age and sex matched 20 healthy controls were included in the analysis. The median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 24 publications
1
25
1
Order By: Relevance
“…This results in agreement with that reported by Karabulut et el. [8] who concluded that serum HGF levels were significant higher in patients with elevated serum ALT levels than others with normal ALT levels (P = 0.05) but in the other hand they found that no correlation between serum levels of HGF and MELD score (P = 0.09), which was in contrast to our results. This difference may be related to difference in patients criteria as the last study included HCV, HBV, alcoholic patients.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This results in agreement with that reported by Karabulut et el. [8] who concluded that serum HGF levels were significant higher in patients with elevated serum ALT levels than others with normal ALT levels (P = 0.05) but in the other hand they found that no correlation between serum levels of HGF and MELD score (P = 0.09), which was in contrast to our results. This difference may be related to difference in patients criteria as the last study included HCV, HBV, alcoholic patients.…”
Section: Discussioncontrasting
confidence: 99%
“…In the presence of liver cirrhosis, the functions of all these cells deteriorate, as do those of parenchymal cells. The mechanism of the high serum HGF level in liver disease could be a disorder of either production or elimination of HGF itself, but the role of HGF in liver disease is complicated and is not yet completely understood [8].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal liver function may be another factor with an influence on HGF. The ALT levels we measured did not differ significantly between the four groups; however, patients with a higher mPAP were more likely to have complications with abnormal liver function and increased levels of ALT, which may upregulate serum HGF levels [22].…”
Section: Discussionmentioning
confidence: 67%
“…In resected HCC patients, high serum HGF levels denote a poor prognosis after hepatic resection [20]. In unresectable HCC, the HGF level has variably been associated with survival time [21, 22]. Moreover, it has recently been proposed that c-Met signaling cooperates with IGFR to increase tumor invasiveness through engagement of the urokinase plasminogen activator system [23, 24].…”
Section: Discussionmentioning
confidence: 99%